Application of the Additive Ratio Assessment (ARAS) Method in Selecting Superior Tourism in the Pasaman District Region - Afrianti, Yusita; Rara Sandhy Winanda (Department of Mathematics, Universitas Negeri Padang (UNP), 2024)
Pasaman Regency has tourism potential, which has not been managed optimally as a whole. Relevant institutions can make improvements to each tourist attraction so that the tourist attractions have the same advantages, so that visitors' interest and interest in visiting each tourist attraction is equal in the future, and regional original income (PAD) will increase from the tourism sector. This research aims to apply the Additive Ratio Assessment (ARAS) Method to select superior tourism in the Pasaman Regency area. The ARAS method will rank tourist attractions in Pasaman Regency based on predetermined criteria. Based on the results of research using the ARAS method, it was found that the most superior tourism attraction was the Ambun Waterpark tourist attraction (A5) with the highest Ki value, namely 0.90231, and the last rank with the lowest Ki value, namely 0.67877, was Taluak Ambun Waterfall (A6).